Facile Synthesis of Cu Quantum Dots‐TiO2 Nanosheets Schottky Junction and Improved Photocatalytic Degradation Activity. Issue 19 (18th May 2020) - Zhai, Siyu; Yang, Xiaoman; Tang, Maoyuan; Gu, Wenhao; Teng, F.
Abstract: Cu quantum dots (CuQDs), which are about 2–4‐nm large, are successfully loaded on the surface of TiO2 nanosheet by a mild and simple method. Under UV light irradiation (λ≤400 nm), CuQDs (10 wt %)‐TiO2 shows a photocatalytic activity 1.9 times higher than TiO2 for the degradation of RhB, although with a lower surface area than TiO2 . The trapping experiment shows that the main oxidation species is . O 2−, which due to the obvious electron migration from TiO2 to CuQDs. The CuQDs loading efficiently improves the photocatalytic activity of CuQDs‐TiO2, which is mainly ascribed to the enhanced charge transfer and separation efficiency by the formation of Schottky junction between CuQDs and TiO2 . Abstract : Cu quantum dots (CuQDs), which are about 2–4‐nm large, are successfully loaded on the surface of TiO2 nanosheet by a mild and simple method. Under UV light irradiation (λ≤400 nm), CuQDs (10 wt %)‐TiO2 shows a photocatalytic activity 1.9 times higher than TiO2 for the degradation of RhB.